Relationship of force variables to vertical jumps performance - de Paula Santana, H. A. (Electronic Theses and Dissertations, 2618, 2016)
The isometric mid-thigh pull (IMTP) has been cited often in the scientific literature; however, there is still a lack of agreement as to the ideal body position used during this test, and how body position impacts the relationship between IMTP performance and dynamic performance. Thus, one aim of this dissertation was to compare two different IMTP positions and correlate the kinetic outputs from each position to vertical jump (VJ) performance. Another purpose of this dissertation was analyze which method of data normalization for IMTP force variables best correlates to squat jump (SJ) and countermovement jump (CMJ) performance.